(3QHeG Jchf (B: (3QSGdI aj GdELeGY hGdGSJUMGHs - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs
(3ChdgG (B:s
.. (3cJHfG aj JMbjb gPG QSGdI eHShWI eTQhMI Ydi Cf GdTHgJjf dG JfaYGf GdCTGYQI Ydi JbOjQ JeGjgeG dCf ebJVGgeG chf GdYHO ZjQ eNJGQ (B... (3hCfg djS dg aYd aEf bdJ aYd LejY eG ChQOJ Ydjge EfeG jQO Ydjge (B..s
(3BNQgG (B:s
.. (3aCf XgQ Gf GdMb eY GdeLJgO (B.. (3hEf XgQ Ydi GdeLJgO Cf GdMb ceG bGd GdYGde acPdc Ef cGf HYO GdefGXQI jchf GdeLJgO Ydi QCjg hGdYGde Ydi GYJbGOg jchf GdMb eY GdeLJgO dCfg ZjQ ZGad hgh (B... (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 17s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs